2006
DOI: 10.1152/ajpheart.00889.2005
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic and parasympathetic component of bradycardia triggered by stimulation of NTS P2X receptors

Abstract: We have previously shown that activation of P2X purinoceptors in the subpostremal nucleus tractus solitarius (NTS) produces a rapid bradycardia and hypotension. This bradycardia could occur via sympathetic withdrawal, parasympathetic activation, or a combination of both mechanisms. Thus we investigated the relative roles of parasympathetic activation and sympathetic withdrawal in mediating this bradycardia in chloralose-urethane anesthetized male Sprague-Dawley rats. Microinjections of the selective P2X purino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…These observations parallel others in which sympathetic blockade attenuated acrolein-induced increases in HRV but parasympathetic inhibition had no such effect 27 . Accordingly, stimulation of a purinergic receptor that mediates reflexes to inhaled cigarette smoke 67 can induce acute bradycardia disproportionately via sympathetic withdrawal 68 . In contrast to its minimal impact during exposure, atropine robustly blunted PG:VG-induced reductions in HRV (SDNN, RMSSD, and HF) late after exposure, implicating parasympathetic withdrawal as an underlying cause of this sympathetic dominance.…”
Section: Discussionmentioning
confidence: 99%
“…These observations parallel others in which sympathetic blockade attenuated acrolein-induced increases in HRV but parasympathetic inhibition had no such effect 27 . Accordingly, stimulation of a purinergic receptor that mediates reflexes to inhaled cigarette smoke 67 can induce acute bradycardia disproportionately via sympathetic withdrawal 68 . In contrast to its minimal impact during exposure, atropine robustly blunted PG:VG-induced reductions in HRV (SDNN, RMSSD, and HF) late after exposure, implicating parasympathetic withdrawal as an underlying cause of this sympathetic dominance.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggest abrupt decrease in cardiac output and cerebral blood flow may have caused irreversible ischaemic damage to the medullary nuclei responsible for cardiorespiratory regulation, resulting in failure to regain cardiorespiratory function 2. Rodent studies have shown that stimulation of the P2X purinoceptors of the NTS produce rapid bradycardia and hypotension, through a combination of reduction in sympathetic outflow and an increase in parasympathetic outflow 8. Previous authors have suggested medullary infarction may disrupt central sympathetic inhibition of the NTS, resulting in reduced sympathetic outflow and increased vagal tone, thereby causing bradycardia and asystole 3.…”
Section: Discussionmentioning
confidence: 99%
“…In the sensitized control rats (n ϭ 7), the adrenalectomized rats (n ϭ 7), and the nonsensitized control rats (n ϭ 7), saline alone (100 l) was injected before administration of the antigen. The doses of the antagonists were previously shown to be effective in inhibiting relevant ␤-adrenoceptors 19 -21 ; the doses of ICI 118,551 0.5 mg/kg 19 and atenolol 2 mg/ kg 20 were reported to effectively antagonize the action of ␤ 1 -and ␤ 2 -agonists, respectively, in rats. The dose of propranolol, 1 mg/kg, is known to inhibit both ␤ 1 -and ␤ 2 -adrenoceptors in rats.…”
Section: Experimental Protocolmentioning
confidence: 98%